Notice to Stakeholders: Questions and Answers on Regulatory Expectations for Medicinal Products for Human Use During the COVID-19 Pandemic - de Farmacoterapia, Revista Portuguesa (2020)
The European Commission, European Medicines Agency and the European medicines regulatory network have developed a question-and-answer document to provide guidance to stakeholders on adaptations to the regulatory framework to address challenges arising from the COVID-19 pandemic. The document was first published in April 2020 and will be updated to address new questions and to adjust the content thereof to the evolution of the pandemic, having already been revised in May 2020. This section attempts to describe a brief summary of the document. The document can be consulted at: https://ec.europa.eu/health/sites/health/files/human-use/docs/guidance_regulatory_covid19_en.pdf.